Kecocokan Jenis Inang dan Pemberian Pupuk Kandang terhadap Pertumbuhan Semai Cendana (Santalum album L. ) - Kuswanto, Kuswanto (Universitas Atma Jaya Yogyakarta, 2005)
The purpose of this research was find out the effects of three host plants and three levels of natural fertilizer on sandalwood seedling growth. This natural relationship between host plant and sandalwood seedling was conducted recognize the characteristic of seedling growth was studied. The parameters were height, diameter, and haustoria number.The research was conducted in factorial experiment arranged in CRD. The treatment consisted of two factors, namely effect of host plant and stable fertilizer. The first factor consisted four kinds of host plants were : a/ control; b/ Cabe rawit ; c/ Turi; and d/ Lamtoro, while the second factor were four levels of stable fertilizer : a/ control; b/ 200 g/pot; c/ 300 g/pot, and d/ 400g/pot.Three replicates was employed in the research.The result of the research indicated that most of different host plant and stable fertilizer treatments were significant effect on sandalwood seedling growth. After five months, the highest growth of Sandalwood seedling treatment with turi and stable fertilizer 400 g/pot was 44.92 cm , and 38.41 cm with host plant cabe rawit and stable fertilizer 300 g/pot. While the lowest was 12.80 cm produced by control (without host plant and fertilizer ). The diameter growth of sandalwood seedling treatment with turi and stable fertilizer 400 g/pot was 3,09 mm, and 3,30 mm with cabe rawit and stable fertilizer 400 g/pot. The houstoria number of sandalwood seedling treatment with turi was 75 and 71 with cabe rawit. In terms of determined the relationship between Sandalwood and its host plants were first turi , second cabe rawit, and lamtoro gung.